Strategy follows structure! - Hall, David; Saias, Maurice A. (Strategic Management Journal, 1980)
Abstract Researchers have for some time been interested in the relationship between the strategy and structure of an organization. In this article the authors discuss the most widely‐held view on the nature of this relationship, and then suggest an alternative explanation. For them strategy, structure, and environment are closely linked. Whereas men may build the structure of an organization, in practice it is this very structure which later constrains the strategic choices they may make.